Keutamaan Ilmu dan Klasifikasi Pendidikan Menurut Al-Ghazali dan Ibnu Qayyim: Perspektif Al-Qur'an dan Hadits - Renda Yastin Nadia; Ainur Rofiq Sofa (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This study examines the virtues of knowledge and the classification of education based on the perspectives of two prominent Islamic scholars, Al-Ghazali and Ibn Qayyim, grounded in the framework of the Qur'an and Hadith. Islam assigns a distinguished position to knowledge, as reflected in Qur'anic verses such as Al-Mujadilah 11, which promises elevated ranks for those who believe and possess knowledge, and the supplication for increased knowledge in Thaha 114. In Hadith, knowledge is likened to beneficial milk that must be shared with others. Al-Ghazali emphasizes the importance of knowledge as a path to happiness in both this world and the hereafter, while Ibn Qayyim highlights the role of knowledge in drawing closer to Allah and shaping a complete human character. This research employs a literature review method to explore the concepts of the virtues of knowledge and education in Islam through the perspectives of Al-Ghazali and Ibn Qayyim. The findings reveal that both scholars present complementary views on the value of knowledge as an act of worship that brings one closer to Allah SWT, while categorizing knowledge based on its benefits for individuals and society. This study underscores that seeking knowledge is an obligation for every Muslim and a path to paradise, as affirmed in the Qur'an and Hadith. These findings provide valuable contributions to the development of Islamic education, particularly in instilling the virtues of knowledge in modern educational curricula.